Ultrasound-Assisted Synthesis of Iron Oxide Nanoparticles: Application in Cytotoxicity and Antibacterial Activity (Iraqi Journal of Medical Sciences, 2025)
Background:    The rapid emergence of antibiotic resistance among various bacterial species has necessitated the development of alternative therapeutic options. Nanotechnology, particularly the production and surface modification of metal nanoparticles (MNPs), has gained significant attention as a promising approach in combating antibiotic resistance.Objective:    To explore a safe and cost-effective method for synthesizing iron oxide nanoparticles (IONPs) with unique shapes through ultrasound-assisted co-precipitation and to use it as a potential solution to the problem of antimicrobial-resistant bacteria especially multidrug-resistant bacteria. Methods: IONPs were synthesized using an ultrasound-assisted method and characterized with techniques such ultraviolet-visible spectrophotometry (UV-Vis), energy dispersive of X-ray spectroscopy (EDX), X-ray diffraction (XRD), atomic force microscopy (AFM), zeta potential analysis, transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Antimicrobial activity was assessed using minimum inhibitory concentration (MIC) tests at 16 μg/ml and a well diffusion assay against Gram-negative bacteria and Gram-positive bacteria.Results: IONPs had an average diameter size of 30 nm, displaying a spherical shape. At concentration of 16 μg/ml, the NPs was found to exhibit a MIC and displayed potent antimicrobial activity against wild-type multidrug-resistant strains of both Gram-positive and Gram-negative bacteria in vitro. Moreover, in vivo experiments showed that the IONPs led to a significant decrease in urothelial bladder cancer (UBC)-40 cell. Conclusion: The US-assisted method utilized in this research for the synthesis of IONPs has proven to be suitable for producing IONPs with precise particle size and high product homogeneity. This efficient synthesis approach holds great promise, particularly in light of the alarming prevalence of multidrug-resistant bacterial strains.Keywords: Fe2O3 NPs, UBC-40 cells, MRS.Citation: Abas SQ, Ahmed ME, Hamid MK. Ultrasound-assisted synthesis of iron oxide nanoparticles: Application in cytotoxicity and antibacterial activity. Iraqi JMS. 2025; 23(1): 92-102. doi: 10.22578/IJMS.23.1.11